The effectiveness of Pectin in the reduction of histological changes caused by exposure to monosodium glutamate in female mice - Al Othman, Sarah Ibrahim; Alanazi, Faten khalif; Sharahili, Ghada Jaber; Alzahrani, Albtoul Abdullah; Shahrani, Razan Dhafer; Alshehri, Wedad Mahdi; Alneghimshi, Anfal Abdulaziz; Albogami, Khlood Safar; Alsiri, Nourah Mohmmd; Almutairi, Shroog Mohammed; Alshwaiqi, Adhwa Suliman (Journal of medical and pharmaceutical sciences, 2020)
Monosodium glutamate (MSG) is widely used as a food additive. Excessive consumption of monosodium glutamate has also been shown to affect the liver and kidneys, causing damage to these tissues because of oxidative stress leading to increased production of reactive oxygen species (ROS). The purpose of the study described in this paper was to find out how the liver and kidney toxicity caused by monosodium glutamate can be mitigated using pectin. To this end, 30 albino mice females were divided into four groups. The animals were distributed in special cages. 12-15 weeks with an average body weight of 60 grams. The animals were divided into four groups: the experimental control group (1) comprising 5 female mice were given normal drinking water and the treated group (2) comprising 10 female mice were given monosodium glutamate at a dose of 3 g/kg body weight in drinking water. For three weeks, the treatment group (3) comprising 10 female mice was given pectin at a dose of 300 mg/70 kg body weight in drinking water immediately after the monosodium glutamate dose for three weeks and the pectin group (4) comprising 5 female mice were given Pectin at a dose of 300 mg/70 kg body weight in drinking water for three weeks. The mice were then anesthetized, dissected, and liver and kidney samples were taken from female mice and kept in a 10% neutral formalin solution to make tissue segments. The results showed many histological changes in the liver, such as congestion of the central vein, widening of the sinuses, and the appearance of signs of the death of most hepatocytes, infiltration of the central vein and an invasion of inflammatory cells around the central vein with the emergence of several gaps within the cells. Many of them cavity with the death of most of the tubule cells, the closure of some of them and the expansion and infiltration in others and bleeding inside the tissue. Pectin therapy has led to the disappearance of most of these changes and the emergence of a clear improvement in hepatic and renal tissue.